HUBUNGAN PERILAKU KONTROL TEKANAN DARAH DAN POLA MAKAN DENGAN STATUS HIPERTENSI DI WILAYAH KERJA UPT PUSKESMAS BATUSURA TANA TORAJA TAHUN 2024 - Claudia Ayu Saputri; Jilly Toar; Ilham Salam (JURNAL ILMIAH KESEHATAN MANADO, 2024)
Hypertension is a condition in which a person experiences an increase in blood pressure beyond a predetermined normal limit of 140/90 mmHg which can result in death. The purpose of this study is to determine the relationship between blood pressure control behavior and diet and hypertension status in the working area of the Batusura' Tana Toraja Health Center. The method of this research is quantitative with a descriptive- analytical approach with a Cross Sectional design. The results of the study with the results of statistical tests on blood pressure control behavior variables and diet, using the SPSS application with the pearson chiu-square test obtained a p-value = 0.000 which means that it is smaller than the decision-making value with a confidence level of 95%, which is α = 0.05. H1 was accepted and H0 was rejected and there was a relationship between blood pressure control behavior and diet with hypertension status in the work area of the Batusura Health Center, Tana Toraja. The conclusion of this study obtained results that prove the hypothesis that there is a relationship between blood pressure control behavior and diet and hypertension status, therefore to pay more attention to be more routine in controlling blood pressure, reducing the habit of eating excessive fatty foods, smoking and increasing physical activity.